Clinical risk analysis of the patient’s path in an Advanced Radiotherapy Center (A.R.C.) through F.M.E.A. method - Pobbiati, Claudio; Monturano, Massimo; Vavassori, Andrea; Gerardi, Marianna; Sarra Fiore, Massimo; Rondi, Elena; Borghetti, Enrica; Castellini, Fabio; Scroffi, Valerio; Arrobbio, Camilla; Castelluccia, Fabiana; Gandellini, Valeria; et al. (Journal of Biomedical Practitioners, 2019)
Starting from the increasing requirement of efficient access to healthcare, the study aims to assess the current standard procedures in order to optimize safety and quality. The decision to study the patient's process in Radiotherapy (RT) by FMEA methodology (Failure Mode and Effect Analysis), in order to identify and manage the risks for patients, arose from an interest of both the Radiotherapy Division and the Management of the European Institute of Oncology (IEO) IRCSS of Milan (Italy) in consideration of its high activity and of the volume of patients treated. The department has undergone a remarkable change in the last seven years, by increasing the number of accelerators and the number of patients treated, which rose from 2.197 (2011) to 3.194 (2017). Treatment modalities and timing of each session have changed: nowadays the majority of the patients receive highly complex treatments (intensity-modulated radiotherapy, image-guided radiotherapy, stereotactic radiotherapy, etc.). Purpose The purpose of this study is to define an instrument of practical use and maintenance, for the proactive management of clinical risk by analysing the patient’s care path in RT: from his medical examination to the discharge and the next follow-up visits. The instrument was tested by handing it out to employees in the form of a questionnaire, trying to involve a significant pool of professionals. Materials and methods Starting from previous Institutional experiences of FMEA studies in other clinical areas, we decided to: make-up several multidisciplinary working groups (with one or two members of each professional level) in order to define the sub-processes, the failure mode and the impact of potential damage. propose the participation of radiotherapy professionals in defining the frequency of the failure mode in their experience, using questionnaires and scales of predefined values. To define the value "potential damage" and the attribution of the frequency of occurrence of the various failure modes, we sought to minimize a potentially non-voluntary effect of mitigating the risk due to the awareness of the correlations between frequency of occurrence and damage. Therefore, the professionals involved were not aware of the results. Results The study was carried out with great participation from the professionals involved in the patient's path (88,6% of the staff involved in the study responded to the questionnaires administered in the first part of the study; 69,7% was the rate of participation in the second part). This result allowed to overcome the subjective limitations due to the low numerical representation and the lack of objective epidemiological data concerning the near miss. Forty-four criticalities were found (14% of all the failure) and required intervention planning. Conclusion This work led to the definition of a model with analytical description and quantification of the clinical risk for all the failure modes by "Risk Priority Number" (RPN) of all the sub-processes of the patient's path. Starting from the significant result of the areas requiring intervention, we could identify several improvement actions to reduce clinical risk. The model allows a dynamic management of clinical risk linked to a specific process and it could be exported to other Radiotherapy Centers.